Development of a Mycelium-Based Thermal Insulation Material - Luksta Ilze; Vamža Ilze; Blumberga Dagnija (Environmental and Climate Technologies, 2025)
The study explores the potential of mycelium-based materials as sustainable thermal insulation for construction. Mycelium, the vegetative part of fungi, grows on organic substrates such as agricultural byproducts, forming a lightweight, biodegradable composite with insulating properties. The experiments focus on optimizing the material’s thermal conductivity and mechanical strength . Mycelium insulation demonstrates thermal conductivity values comparable to traditional materials like mineral wool and expanded polystyrene (EPS), with a range of 0.039 to 0.05 W/m·K. The production process employs renewable resources, is non-toxic, and aligns with circular economy principles by repurposing agricultural waste. Challenges remain in enhancing water resistance and mechanical adaptability. The findings underline mycelium’s potential as an eco-friendly alternative in modern sustainable construction, emphasizing its role in reducing carbon footprints and promoting resource efficiency.